Prediction of FLD using Abaqus and Gurson Model for Simple Flat Spacemen - Domokos, Tatiane; Baksa, Attila; Szávai, Szabolcs (International Journal of Engineering and Management Sciences, 2023)
In the past century, in many industries, such as, metal forming industry, it has been important to predict ductile damage and fracture of metals under complex loadings. Regarding damage mechanics, one of the most classical models is the GTN, which was originated from Gurson and later enhanced by Tvergaard and Needleman. The inprovement was achieved by introducing an equivalent void volume fraction f and two more parameters called q1 and q2 into the yield function of Gurson’s model.